Detection of heart murmurs - Chia, Miao Juan. (2011)
Heart murmurs are abnormal sounds during a heartbeat cycle [1]. These sounds, caused by the turbulent blood in the heart, are traditionally detected by auscultation. However, the analysis based on these heart sounds is often subjective and unreliable. This project aims to refine the diagnosis process by developing a heart sound analyzer to identify the heart sound components as well as murmurs.